The eating habits, consuming foods, and body mass index of elderly people registered in a family health center in Samsun - Avci, Ilknur Aydin; Altin, Alaattin; Sökülmez Kaya, Pinar (Progress in Nutrition, 2016)
Aim: This study aims to determine the eating habits of people 65 years of age and above. Method: This cross sectional study was done using survey forms in face-to-face interviews with 276 people 65 years of age and above at a family health center. The participants’ Body Mass Index values were calculated on the basis of their weight and height. Descriptive statistics and chi-square test were used for data analysis. Results: The average age of the participants was 71.4±6.2 (minimum=65, maximum=96). Of them, 51.8% were primary school graduates, 46.7% were slightly overweight, 64.1% had health problems, 63.0% regularly used medicines, and 45.7% ate 3-4 meals a day. First-degree obesity was found in 58.3% of the elderly women, 50.0% of the primary school graduates, 75.0% of those who regularly used medicines and 73.3% of those with health problems. Of these elderly people, 28.6% said they were informed about nutrition. Conclusions: This study indicated that elderly people were not sufficiently informed about nutrition, that women were fatter than men according to their BMI, and that most of these elderly people were overweight and obese. Developing healthy eating habits and a well-balanced diet in old age will promote a better quality of life and healthier aging.